(untitled) (Islamic Sciences Journal, 2024)
ABSTRACT The book of Al-Ahkam Al-Sultaniyyah by Al-Mawardi and Al-Farra’ are in the hands of people. Their title is the same, their subject is the same, their arrangement is the same, and everything in them is the same, and their authors lived in the same era and in one country, and both of them were judges, and the identicalness may reach entire pages without change, except that Imam Al-Mawardi mentions the opinions of the Hanafi school of thought. The Malikis and Shafi’is then often adhere to his school of thought, while Imam Al-Farra only mentions the opinion of the Hanbalis. Therefore, we find that the book of Imam Al-Mawardi is more based on verses, hadiths and poetry than Imam Al-Farra’, and this is not surprising, since the methodology of writing the first in his work requires mentioning the evidence for each doctrine and discussing it, and most of the researchers’ opinions agreed that the two works are related to each other before and after, and that they quote one from the other, but They disagreed about (Who took it from whom?) and (Who came first in the classification?), to the point that some researchers argued that the work is the same, but it is not known who it is for due to the extent of similarity and identicalness. Some of them argued that they had a previous work and were quoted from them, but this is far-fetched. Some of them stopped in resolving the issue and did not reach anything. Some of them believed that Imam Al-Farra was the first in the classification and that Imam Al-Mawardi was the one who quoted from him. And some of them suggested that Imam Al-Mawardi had precedence in the classification and that Imam Al-Farra was the one who quoted a lot of it, and this is what we have proven. With certainty. This is by God, Glory be to Him, Most High and Most Knowing, and our last supplication is that praise be to God, Lord of the worlds, and may God Almighty’s blessings and peace be upon Muhammad and his family and companions.